PENGELOLAAN PERIKANAN TONGKOL LISONG (Auxis rochei) DI KAWASAN KONSERVASI PERAIRAN NUSA PENIDA, BALI - Yuliana, Ernik; Nurhasanah; Yani, Diarsi Eka; Agustina, Siska (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Nusa Penida is a marine protected area that has a high diversity of fish. Fishing of target fish is need to be properly regulated and managed to avoid overfishing. The aim of the study was to assess the management of bullet tuna (Auxis rochei) fishing in Nusa Penida using the EAFM indicators. The research conducted in Nusa Penida, Bali Province, on July-December 2018. Primary data collected includes ecological data (fish length and weight, and water quality) by survey to fish catches and waters; and socio-institutional data collected by distributing questionnaires to 54 respondents (drift nets, gill nets, hand line), and interviews with stakeholders. Data analysis was carried out descriptively. The results indicated that the bullet tunas had an average length of 24.59 cm with range of 21-34 cm, smaller than the size range recorded in the fishbase of 35-50 cm. The spawning potential ratio value is 23%, which indicates overfished. Water quality is in accordance with seawater quality standards for marine biota. The implementation of traditional wisdom, namely Nyepi Segara, is adhered to by the local community. Assessment of bullet tuna management using EAFM indicators concluded that in the fish resources domain there were indications of overfished. Habitat domain (water quality and coral cover) is good. On the social aspect, the results are good, except that the respondent's income (54%) is less than IDR 1,500,000.00.